A Discharge Time-Out: A Case Study on Physician–Nurse Discharge Communication and the Challenge of Sustainability in Resident-Led Quality Improvement. (July 2019) - Raffel, Katie E.; Gupta, Neha; Vercammen-Grandjean, Christopher; Hohman, Jessica; Ranji, Sumant; Pierluissi, Edgar; Mourad, Michelle
Resident-led quality improvement (QI) is an important component of resident education yet sustainability of improvement and impact on resident education have rarely been explored. This study describes a resident-led intervention to improve nursing (RN)–provider (MD) communication at discharge—the Discharge Time-Out (DTO)— and explores its uptake and sustainability. One year later, residents were surveyed regarding QI self-efficacy and planned QI involvement. Baseline verbal RN–MD communication at discharge was rare. During DTO implementation, rates of structured communication averaged 56% (341/608) with several months >70%. During the monitoring phase, this fell to 45% and did not recover (833/1852). Participating residents reported increased QI self-efficacy ( P < .05) and increased likelihood of participating in future QI ( P < .05). The DTO increased RN–MD communication but was not sustained. Resident-led QI should explicitly address sustainability to achieve improvement and educational objectives. To foster resident education and avoid short-lived, low-impact projects, increased attention should be given to sustainability of resident-led QI.